The Divertor Tokamak Test facility proposal: Physical requirements and reference design. (August 2017) - Crisanti, F.; Albanese, R.; Granucci, G.; Martone, R.; Sonato, P.; ,
Highlights: The DTT (Divertor Test Tokamak facility) proposal is aimed at demonstrating a heat exhaust system capable of withstanding the large load of DEMO in case of inadequate radiated power fraction. DTT has the flexibility to test a wide set of divertor concepts and techniques including alternative magnetic configurations and liquid metal targets. The basic physical DTT parameters have been selected so as to have edge conditions as close as possible to DEMO in terms of dimensionless parameters within an upper bound of 500 M€ for the investment costs. Abstract: The main goal of the Divertor Tokamak Test facility (DTT) is to explore alternative power exhaust solutions for DEMO. The principal objective is to mitigate the risk of a difficult extrapolation to fusion reactor of the conventional divertor based on detached conditions under test on ITER. The task includes several issues, as: ( i ) demonstrating a heat exhaust system capable of withstanding the large load of DEMO in case of inadequate radiated power fraction; ( ii ) closing the gaps in the exhaust area that cannot be addressed by present devices; ( iii ) demonstrating how the possible implemented solutions (e.g., advanced divertor configurations or liquid metals) can be integrated in a DEMO device. In view of these goals, the basic physical DTT parameters have been selected according to the following guidelines: ( i ) edge conditions as close as possible to DEMO in terms of dimensionless parameters; ( ii ) flexibility to test a wide set of divertor concepts and techniques; ( iii ) compatibility with bulk plasma performance; ( iv ) an upper bound of 500 M€ for the investment costs.